Functional and aesthetic correction of secondary unilateral cleft lip nasal deformities - Cohen Mimis; Morris David; White Aisha; Patel Pravin (Indian Journal of Plastic Surgery)
The treatment of patients with unilateral cleft lip has undergone significant development during the last decades. With better understanding of the anatomy of the unilateral cleft lip and nasal deformities, primary correction of the nasal deformity at the time of lip repair, critical evaluation of short and long-term results following various treatment protocols, and constant striving for perfection in both aesthetics and function, we have been able to design improved treatment strategies and more accurate surgical techniques so as to achieve overall superior and long-lasting results. In this review article, we present our protocols and experience for functional and aesthetic correction of secondary unilateral cleft lip nasal deformities and a retrospective review of 219 consecutive patients treated at our Craniofacial Centre for correction of secondary unilateral cleft lip nasal deformities. The protocols used in the treatment of 219 consecutive patients at our Craniofacial Centre for correction of secondary unilateral cleft lip nasal deformities were reviewed. In addition, analysis of the most recent 51 consecutive patients who underwent complete clinical and functional evaluation with rhinomanometry followed by correction of the cleft lip nasal deformity was performed. A variety of time-honoured techniques of rhinoplasty were applied in the correction of the residual deformities to achieve symmetry, aesthetic balance, and functional correction of the nose. Follow-up ranged from 5-11 years. Analysis of the data revealed that 39 patients (76.47%) had significant functional and aesthetic improvement; seven patients (13.07%) had significant aesthetic improvement but a modest functional improvement; and five patients (9.8%) required additional surgery to improve their appearance and had no functional improvement. Further analysis demonstrated that five out of seven patients in the second group had pharyngeal flaps in place that were primarily responsible for the airway obstruction. No attempt was made to revise the ports of these flaps because the speech was excellent. The surgical plan is based on the information gained from our extensive clinical evaluation and is tailored to the patient′s specific functional and aesthetic needs.